Roof architectural finishes (RFA-426_Rev A) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture; Web Structures (2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.